A review of the Islamic approach in public health practices - Abdul Rahman, Anita; Mahmud, Aidalina (Community Health Society Malaysia, 2014)
Public Health’s aspiration has always been to provide a comprehensive system in which the whole population, not merely individuals, can be healthy. Sadly, religion particularly Islam, is rarely associated with Public Health in this modern era, perhaps because people are complacent and preoccupied with worldly knowledge. Islam considers health as a basic human right and much success in Public Health history and activities have actually been linked to some of the Islamic approaches. Hand washing procedures and encouragement of breastfeeding are examples of Islamic basic practices. The incorporation of these measures into public health practices has greatly contributed to the health of the population and increased life expectancy. However literature on the relation between Islam and Public Health is scarce and one of the reasons is probably because those Islamic references were written in the Arabic language, which many do not understand. Therefore the aim of this article is to share some of the evidence of Islamic practices based on the Qur’an and Sunnah in various aspects such as knowledge, practical prevention and health care which played a key role and pioneer in the field of Public Health.